2002
DOI: 10.1046/j.1365-2338.2002.00598.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of Pepino mosaic potexvirus in tomato

Abstract: At the beginning of 1999, a new virus disease occurred in protected tomato crops in The Netherlands. Initial diagnostic tests revealed the presence of a potexvirus but serological tests ruled out the presence of Potato X potexvirus (PVX). Tests for other potexviruses reported from solanaceous crops provisionally identified the virus as Pepino mosaic potexvirus (PepMV). The virus was purified, and an antiserum was produced, which showed strong reactions with both the type isolate of PepMV from pepino and two ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
1
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 7 publications
4
19
1
1
Order By: Relevance
“…Black Beauty show that symptom development is dependent on both locality and virus type. Variation in symptom development was also reported by Papayiannis et al (2012), who found no symptoms in Cyprus with EU-tom and Ch2 group isolates; by Salomone and Roggero (2002) reporting local and systemic symptoms in Italy with an EU-tom group isolate; by van der Vlugt et al (2002) finding no local, but systemic symptoms by an EU-tom group isolate in the Netherlands; and by Pospieszny et al (2008) finding systemic symptoms in Poland by an EU-tom and Ch2 group isolate.…”
Section: Discussionsupporting
confidence: 54%
See 4 more Smart Citations
“…Black Beauty show that symptom development is dependent on both locality and virus type. Variation in symptom development was also reported by Papayiannis et al (2012), who found no symptoms in Cyprus with EU-tom and Ch2 group isolates; by Salomone and Roggero (2002) reporting local and systemic symptoms in Italy with an EU-tom group isolate; by van der Vlugt et al (2002) finding no local, but systemic symptoms by an EU-tom group isolate in the Netherlands; and by Pospieszny et al (2008) finding systemic symptoms in Poland by an EU-tom and Ch2 group isolate.…”
Section: Discussionsupporting
confidence: 54%
“…Isolates from three PepMV strains were included in the trials: 1) isolate PD99901066 belonging to the EU-tom strain (Van der Vlugt et al 2002), 2) isolate PCH06/104 belonging to the Ch2 strain (Hanssen et al 2008), and 3) isolate US1-PRI (US1 strain). The isolates were distributed to different laboratories as freeze dried leaf material of PepMV infected N. benthamiana.…”
Section: Isolates Propagation and Inoculation Proceduresmentioning
confidence: 99%
See 3 more Smart Citations